Opening and closing asymmetry: empirical analysis from ISE Xetra - Kelly, Robert J. (Economic & Social Studies, 2008)
Overnight news yields difficulties for price discovery at market opening culminating in additional return volatility. Biais et al. (2007) show opening prices are sensitive to order flow from the pre-trading session. We investigate the existence of volatility asymmetry between opening and closing returns and trader over-reaction on the Irish Stock Exchange (ISE). Opening on the ISE follows a non-transparent pre-trading session. We estimate opening returns are 10 per cent more volatile than closing returns. This is significantly smaller compared to other exchanges, such as LSE. The LSE operates under a transparent pre-trading session, which is susceptible to order flow manipulation. We implement an ARMA(1,1) framework to investigate the speed of trader reaction to news. Over-reaction is recorded at the morning auction but is smaller in magnitude when compared to international markets with transparent pre-trading and `non-binding? orders. The level of price reversal bolsters the over-reaction argument. We estimate a 30 per cent reversal of overnight returns with one third taking place in the first thirty minutes of trading.
Paper delivered at the Twenty-First Annual Conference of the Irish Economic Association, Bunclody, Co. Wexford, April 25?27, 2007
Keywords: Stock market; Trading; Ireland; Share prices